"Communities in the middle": Interactions between drivers of change and place-based characteristics in rural forest-based communities. (December 2015) - Morzillo, Anita T.; Colocousis, Chris R.; Munroe, Darla K.; Bell, Kathleen P.; Martinuzzi, Sebastián; Van Berkel, Derek B.; Lechowicz, Martin J.; Rayfield, Bronwyn; McGill, Brian
Abstract: Using a socioecological systems perspective, we advance a conceptual approach for characterizing trajectories of change in rural forest-based communities. We call attention to "communities in the middle, " communities positioned within forested regions representing neither unpopulated wilderness nor heavily urbanized or densely populated places on the edge of urban areas. In 2010, these middle places accounted for 27.3% of the continental United States landscape yet less than 5% of the human population. Common shocks, such as the decline of traditional production industries, demographic shifts, new information technologies, climate change, invasive species, and demand for new energy resources, unite these areas. Yet, we observe variation in existing patterns of change across communities, which grows out of interactions between local contexts and larger drivers of change. Focusing on community dynamics, structure, and well-being in transitioning rural forested landscapes, we synthesize insights on three commonly identified development trajectories. We identify interactions among the resource base, connectivity to other places, and social adaptability as critical to these trajectories. Further, we describe vulnerabilities, opportunities, contingencies, diversity, novel recombinations, and mitigation as useful concepts for understanding community pathways within these trajectories. This framework provides a starting point to guide further synthesis, formal meta-analyses, and future interdisciplinary research on change in these important 'middle' places. Highlights: Rural areas contain key components for sustaining forested socioecological systems. Trajectories of community development share complex characteristics. Interaction of local and extralocal dynamics drives variation in these trajectories. Rigid disciplinary or regional models neglect interplay of cross-scale dynamics. A "Communities in the middle" framework synthesizes and advances rural studies.